Developing an Operational Approach to Educational Quality Assurance in Colleges under the Office of the Vocational Education Commission in Thailand - Ch. Chianchana; S. Na Wichian (Образование и наука)
Introduction. Improving quality assurance requires vocational education to be consistent and to be appropriate with the context of the school education. The school quality assurance operations are a driving mechanism for achieving high educational results at the next stages of education. This process will result in sustainably improving education quality. The research aims were to assess the conditions for improving the quality of education in colleges under the Office of the Vocational Education Commission (OVEC) and to analyse and evaluate the operational approach to ensuring the quality of education. Methodology and research methods. The study participants included college personnel directors, teachers, and staff selected through purposive sampling. A total of 44 participants were recruited for the context assessment: 28 people to analyse the operational approach and 39 people to assess the operational approach. The research tools included a record form to provide an educational quality assurance context, a questionnaire to determine the operational approach of educational quality assurance, and an assessment form to determine the operational approach of educational quality assurance. The data were analysed using percentage, mean, standard deviation, odds ratio, and content analyses. Results and scientific novelty. The research results show that the similar contexts of education at all courses are the standard of vocational management and the standard for creating a society of learning (cooperation in creating a society of learning). Meanwhile, the differences identified are related to the peculiarities of professional qualifications and various standards for creating a learning society (innovation, inventions, creative work and research). The analysis of the operational approach allowed the authors to find out eight internal quality assurance factors for educational quality assurance: educational quality assurance planning; design of education quality assurance; study focusing on the actual operations; following the process; selection of quality indicators and criteria according to the educational context; efficient data management; following and monitoring assessments; and reviewing revised or edited assessments. Moreover, four external quality assurance factors are identified: evidence for educational quality assurance; accreditation of educational quality assurance; assessors holding appropriate qualifications; and judgment of the assessment results. In the course of the operational approach assessment, it is established that there are high levels of feasibility and appropriateness in all aspects. The operational approach to educational quality assurance was developed using the context analysis, inputs, processes, results and concepts of internal and external quality assurance through evidence of cross-impact analysis. This method of analysis can be used to respond to educational quality assurance policy that requires that the demonstrated approach is to be easily applied in practice and requires the use of both quantitative and qualitative methods, thus creating innovations in the field of productivity-enhancing and their application in vocational education. Practical significance. The research results can be useful for directors, teachers and staff at colleges and the Office for National Education Standards and Quality Assessment in Thailand to design and develop the methods for achieving improved quality of education on a sustainable basis.